Handbook of digital signal processing engineering applications - Elliott, Douglas F. (San Diego : Academic Press, 1987)
FROM THE PREFACE: Many new useful ideas are presented in this handbook, including new finite impulse response (FIR) filter design techniques, half-band and multiplierless FIR filters, interpolated FIR (IFIR) structures, and error spectrum shaping.
Includes bibliographical references and index.
Keywords: Signal processing -- Digital techniques -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc